Adorno and the concept of genocide - Crawford, Ryan (Value inquiry book series. Holocaust and genocide studies., 2016)
Adorno and the Concept of Genocide examines the legacy of Critical Theory's foremost authority on life 'after Auschwitz.' As a leading member of the Frankfurt School and one of post-war Europe's most important public intellectuals, Adorno's reflections on genocide and its relation to contemporary society achieved a level of urgency and insight that remains unparalleled to this day. Assembled here for the first time in English is a wide-ranging collection of essays on the seminal significance of the concept of genocide for Adorno's thought, as well as the enduring relevance of that thought for our own time. Contributors include: Babette Babich, Ryan Crawford, Tom Huhn, Osman Nemli, Ulrich Plass, Erik M. Vogt, James R. Watson, Markus Zöchmeister.